Siderophore cheating and cheating resistance shape competition for iron in soil and freshwater Pseudomonas communities - Elena Butaitė (Nature Portfolio, 2017)
Lab strains of Pseudomonas are model systems for the evolution of cooperation over public goods (iron-scavenging siderophores). Here, Butaitė et al. add ecological and evolutionary insight into this system by showing that cheating and resistance to cheating both shape competition for iron in natural Pseudomonas communities.